PERNIKAHAN ANAK USIA DINI DITINJAU DARI PERSPEKTIF UNDANG-UNDANG NEGARA REPUBLIK INDONESIA DAN DALAM KONTEKS HUKUM ISLAM - Adha sianipar, Solehah Dhara (Journal Analytica Islamica, 2023)
This research is based on the author's desire to find out how the law is applied in the country of Indonesia and from the perspective or view of Islamic law related to the issue of early child marriage to see whether in a legal view both such things are permissible or violate some norms, both social norms , religious norms, and other norms. The research method used is normative law or library law research. Early marriage is a social phenomenon that often occurs in various regions. The phenomenon of early marriage is like an iceberg phenomenon that only appears to be a small part on the surface, very little is exposed in the public domain, but in reality it happens a lot in the wider community. When we trace the historical roots of early marriage in Indonesia, especially on the island of Java, it has actually become something that was commonly done by our grandparents. In their context, there is a negative stigma if a woman marries at a mature age in their community. This paper will discuss the phenomenon of early marriage in the context of Islamic law and based on Indonesian child protection laws.